Reparación de moto marca Honda modelo CB650 SC del año 1982 - SILVA GUARANDA, EDISON ALFONSO (2015)
project was to repair a Honda motorcycle, model CB 650 SC 1982 which has a 4-stroke engine and 4 Cylinder offline with carburetors and exhaust Independent; this motorcycle was awarded in 2010 by the magazine " Worldcycle " who named one of the " best used motorcycles.” The purpose of this work is to verify qualifications , analyzing and correcting the various faults that have the engine, brake systems, electrical and electronic components as well as the different fluid leaks for Honda motorcycle, model CB 650 SC 1982 . This work was performed by observing the directions and recommendations set by the manufacturer through the manual of preventive and corrective maintenance for motorcycles Honda CB 650 SC in conjunction with the application of knowledge acquired in the career of Technology in Automotive Mechanics of the prestigious alma mater